13‐Cis retinoic acid can enhance the antitumor activity of non‐replicating Sendai virus particle against neuroblastoma. Issue 2 (7th December 2012) - Nomura, Motonari; Shimbo, Takashi; Miyamoto, Yasuhide; Fukuzawa, Masahiro; Kaneda, Yasufumi
<x xml:space="preserve">Abstract</x> Hemagglutinating virus of Japan‐envelope (HVJ‐E) is a drug delivery vector based on inactivated Sendai virus. Recently, antitumor activities were found for HVJ‐E itself and clinical trials of HVJ‐E for some malignant tumors are now ongoing. We investigated the in vitro and in vivo antitumor effects of HVJ‐E against neuroblastoma, which is one of the most common malignant solid tumors in childhood. The sensitivity of human neuroblastoma cell lines to HVJ‐E correlated with the expression level of gangliosides, Sialylparagloboside (SPG) and GD1a, receptors for HVJ. Among the cell lines, SK‐N‐SH was the most sensitive to HVJ‐E in vitro and total SPG and GD1a expression was the highest. Complete eradication of subcutaneous tumors derived from SK‐N‐SH cells was achieved by intratumoral injection of HVJ‐E in SCID mice and no recurrence was observed for more than 300 days after HVJ‐E inoculation. In contrast, NB1 cells expressed the lowest amount of GD1a and SPG and were resistant to HVJ‐E in vitro. The expression of GD1a increased by 13‐cis retinoic acid (13cRA), which is a therapeutic drug for high risk neuroblastoma, thus leading to an improved sensitivity to HVJ‐E in vitro. Only growth inhibition of the subcutaneous tumors derived from NB1 cells was achieved by HVJ‐E in the SCID mice, but the combination of 13cRA and HVJ‐E could achieve partial eradication of the xenograft and also lead to an improved prognosis. In conclusion, HVJ‐E is a promising therapeutic modality for neuroblastoma and 13cRA can be used as an adjuvant to HVJ‐E.